Action of low-level laser therapy on the healing of diabetic ulcerations (Research, Society and Development, 2020)
The objective was to verify evidence in the literature about the effectiveness of low-level laser therapy in the tissue repair of diabetic foot ulcers. An integrative literature review was carried out through the online research platforms Us national Library of Medicine (PUBMED) and Virtual Health Library (VHL) in the LILACS, MEDLINE AND BDENF databases. For the elaboration of the research question of the integrative review, the PICO strategy was used, fundamental for the improvement of the specificity and conceptual clarity of the clinical situation to be studied, returning results of greater quality and precision. Articles indexed in national and international journals were selected, made available in full, research involving human beings without distinction of gender, and studies comprised in the last 5 years in all languages ​​found. The results obtained demonstrate proven efficacy in the treatment of diabetic ulcerations through the cellular stimulation provided by the laser, which results in greater cell proliferation, neovascularization, and collagen synthesis. Therefore, the Laser is important because it is a low-cost therapy alternative to the conventional treatment of diabetic ulcers, which offers scientific evidence in the process of tissue repair and reduction of the injured área.